Banking on Growth Models : China's Troubled Pursuit of Financial Reform and Economic Rebalancing - Bell, Stephen, 1954-; Feng, Hui, 1972- (Book collections on Project MUSE., 2022)
"This book examines the evolution and dynamics of China's banking and financial system since the late 1970s and links this to the changing dynamics driving China's economic growth model. The book explains how China's phenomenal growth trajectory has been built on a highly politicized and inefficient banking and financial system, and how this has increasingly undermined China's market transition and economic rebalancing."--